THEORY IN PRACTICE : INCREASING PROFESSIONAL EFFECTIVENESS - ARGYRIS, Chris (Jossey-Bass Pub. San FranciscoUS, 1974)
Seeks to lay the foundations for understanding and explaining human actions especially within the framework of an organization. Defines learning in terms of outcomes and processes. Breaks down the observable process of learning as follows: discovery of a problem; invention of a solution; production of a solution; and, monitoring the implementation.